Valoración del Instrumento de Evaluación de las Prácticas Preprofesionales de la Carrera de Odontología - Díaz López, Cecilia Mariana (2024)
Evaluation instruments are tools that enable teachers to assess the level of learning achieved by students and allow students to identify their strengths and recognize their level of knowledge. To delve deeper into this topic, the present research aims to assess the evaluation instrument used in pre-professional practices in the Dentistry Program at Universidad Nacional de Loja, focusing on a qualitative, observational, descriptive, and cross-sectional approach. In the methodological process, a content analysis of the instrument was carried out using a checklist, with the following rating scale: excellent, very good, good, sufficient, and deficient. To understand the thoughts of students and teachers regarding the evaluated instrument, data collection techniques such as a focus group and an interview were applied. The results indicate that the evaluation instrument is good, meaning it meets some quality standards. However, students' criteria focus on the tool's function of evaluating for promotion, although it is evident that the structure of the instrument does not allow for quality assessment, as it evaluates general procedures, lacks self-assessment, and has unclear grading parameters. For teachers, this document is inadequate as it lacks clear evaluation indicators, resulting in subjective grading. It also does not facilitate adequate feedback, and although it helps to obtain evidence of the student's work, it does so in a general manner. In conclusion, it was evident that the instrument lacks a clear format, instructions, observations, objectives, dimensions, evaluation indicators, and an overall average to make a judgment on the performed practice. Keywords: Evaluation Instruments, Teaching, Learning, Pre-Professional Practices, Quality, Clinical Practices.